Evolution of twinning systems and variants during sequential twinning in cryo-rolled titanium. (January 2019) - Huang, Z.W.; Jin, S.B.; Zhou, H.; Li, Y.S.; Cao, Y.; Zhu, Y.T.
Abstract: On the basis of the order in which twinning occurs, twins are termed primary, secondary, and tertiary. In HCP materials, compression twins (CT) and extension twins (ET) are observed to form alternatively during sequential twinning. However, selections of twinning systems and variants are not yet fully understood. Both ET→CT→ET and CT→ET→CT sequences have been reported in literatures. Here we conduct a systematic and statistical study on the evolutions of twinning sequences and variants during cryogenic rolling of Ti. Both twinning sequences are observed in the same sample. Current statistical results indicate the selections of the twinning sequence and variants are governed by the following criteria: (1) the twinning sequence in an individual grain depends on its initial orientation; (2) the twin variant selection is mainly governed by the Schmid's law, although a few non-Schmid twins are observed along the short axis of the parent grains. These criteria are thought applicable to other HCP metallic materials. Highlights: Both ET→CT→ET and CT→ET→CT twining sequences were found in a LNT-rolled Ti sample. Grain orientation dominates twinning systems variation in twinning sequence. Schmid law can primarily explain the twin variant selection in twinning sequence. The formation of low Schmid factor twin could be attributed to the low twinning free path.